Hell as a Geological Construct - Burrell, Margaret (Florilegium, 2007)
Two documents dated from the ninth century speak of two concurrent locations of hell and both contain details of a high burning mountain and a burning pit. The better-known text is the Latin Navigatio sancti Brendani abbatis, the account of which spurred Tim Severin in the late 1970s to take the route supposedly taken by St. Brendan and to assert that the volcanic activity off the coast of Iceland was the most likely source of the phenomena described. Since volcanic eruptions can be dated accurately to within fifty years, this paper has used the geological data available to locate more precisely the likely eruption which gave rise to accounts of the terrestrial locations of hell. In addition, this paper uses geological details of Irish cave systems to suggest a location of the Purgatory of Saint Patrick alternative to that which is currently accepted.